PERAN KOMUNIKASI DIDAKTIK, PEMBELAJARAN KOLABORASI, DAN KINERJA GURU PADA HASIL BELAJAR MELALUI MOTIVASI BELAJAR - Anditya Handoko; Muhammad Abdul Ghofur (Universitas Muria Kudus, 2020)
This study aims to determine the effect of didactic communication, collaborative learning, and teacher performance on learning motivation in Economics Subjects in class XI IPS at SMAN 1 Purwosari, also to determine the effect of learning motivation on student learning outcomes. This research is a type of quantitative research. The data analysis technique used is structural equation modeling (SEM) analysis. The data used came from 107 respondents collected from March to April 2019. The results of this study indicate that only collaborative learning variables affect learning motivation, but learning motivation has no significant contribution to learning outcomes. Didactic communication variables and teacher performance were also not confirmed to have a substantial effect on learning motivation.